Rancang Bangun Sistem Informasi Pengingat Jadwal Pembayaran Angsuran Pada Bank BPR NBP 15 Kabanjahe Berbasis SMS Gateway - Dewi Yohana Br Ginting; Raynaldy Kurniawan Keliat (Institut Teknologi dan Bisnis Indonesia, 2025)
A corporation called PT. BPR NBP 15 Kabanjahe Karo works in banking finance and facilitates borrowing and investing for the general people. Issues occur when the current system is still traditional, making it less efficient for clients to easily and quickly learn about the Bank's payment maturity information. The goal of this study is to put in place a reminder system that will automatically notify PT members when their payments are due. There are fifteen players in the NBA. An SMS gateway may be thought of as a conduit for transmitted and received SMS data flow. According to the tests that have been conducted, the loan date and the payment deadline are entered to determine the installment payment date. Based on this study, it can be clearly determined that PT. BPR NBP 15 Kabanjahe Karo could significantly optimize payment information to consumers by implementing a reminder SMS function. Each client would get timely reminders via SMS based on the installment amount and due date at PT. BPR NBP 15.